Optimalisasi Load In Coal Handling Facility 4 (CHF 4) Site Banko Barat di PT Bukit Asam Tbk - Tri Yeli Marsa; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Bukit Asam Tbk, has a belt conveyor load in and load out system of each coal handling facility in the coal production unit. The conveyor belt at PT Bukit Asam has the same size as the TPH which varies according to the capacity needed per each conveyor belt for coal delivery will differ according to the shipping path. for conveyor belt production capacity will depend on the minimum production capacity. PT. Bukit Asam in 2019 determines an increase in production targets of 26 Million ton Thus, an optimization is needed so that the loading lanes at the coal handling facility 4 (CHf 4) can be used properly.in this research, combined theory with field data, in order to obtain problem solving. And the results of data processing will be analyzed so that it can later be produced at a meeting.Based on the results of research conducted can conclude the following points. First, the actual capacity of the dump hopper is 263,600 tons with a mechanical capacity of 250,000 tons. The second minimum belt conveyor production capacity in shipping coal to the stockpile is 775.00 tons / hour. Third, some anticipations to increase production targets include: selective mining, redesign of dump hopper 2.1 and routine checking of units before operation. Fourth, change the diameter of the drum instead of raising the front belt from4.8 m / s to5.2 m / s.Keywords: Produktivitas, Belt Conveyor, Load In, Coal Handling Facility, Dump Hopper, Production